Chemerin deficiency regulates adipogenesis is depot different through TIMP1 - Cheng-Long Huang; Liu-Ling Xiao; Min Xu; Jun Li; Shu-Fen Li; Cui-Song Zhu; Yu-Li Lin; Rui He; Xi Li (Genes and Diseases, 2021)
Adipocytes and immune cells are vital for the development of adipose tissue. Adipokines secreted by adipocytes regulate adipogenesis and body metabolism. Chemerin is one of the adipokines. However, the function and mechanism of chemerin in adipose tissue are not fully illuminated. Compared with wild type (WT) mice, Rarres2−/− mice gained weight and significantly increased fat distribution in subcutaneous adipose tissue (SAT), rather than visceral adipose tissue (VAT) on high fat diet (HFD). PPARγ and C/EBPα, the master regulators of adipogenesis, were up-regulated in SAT and down-regulated in VAT in Rarres2−/− mice comparing with WT mice. Inspite of chemerin deficiency or not, the ratio of adipocyte-progenitors to total cells and the differentiation capacity of adipocyte-progenitors were similar in SAT and VAT, but macrophage infiltration in VAT was more severe than in SAT in Rarres2−/− mice. Furthermore, CD45+ immune cells supernatant from Rarres2−/− SAT promoted the differentiation of adipocyte-progenitors and 3T3-L1 cells. Adipokine array assay of CD45+ immune cells supernatant revealed that metalloproteinase inhibitor 1 (TIMP1), an inhibitor of adipogenesis, was reduced in Rarres2−/− SAT, but increased in Rarres2−/− VAT. As we specifically knocked down chemerin in SAT, TIMP1 was down-regulated and adipogenesis was promoted with reducing infiltration of macrophages. The present study demonstrates that the effects of chemerin on adipose tissue is depot different, and specific knock down chemerin in SAT promote adipogenesis and improve glucose tolerance test (GTT) and insulin tolerance test (ITT). This suggests a potential therapeutic target for chemerin in the treatment of obesity related metabolic disorder.